2010
DOI: 10.1088/0967-3334/31/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Automatic quantification of the Poincaré plot asymmetry of NN-interval recordings

Abstract: We investigated the electrocardiographic substrate underlying the asymmetry of Poincaré plots of NN intervals (NNI) on different time scales and conceived a method for automatic asymmetry quantification (AQUA), which is based on the observation that left-sided comet asymmetry (A(L)) is due to sudden increases (SIC), and right-sided comet asymmetry (A(R)) to sudden decreases (SDC) of cycle lengths, and that both the SIC and SDC episodes were consistently associated with significant changes in P-wave magnitude a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our study, in accordance to the work of other research groups (Esperer and Oehler 2010, Karmakar et al 2009, Piskorski and Guzik 2007, Porta et al 2008, clearly detected HRA. According to our investigation, HRA is the reflection of and could be influenced by the ratio of inspiration/expiration duration.…”
Section: Discussionsupporting
confidence: 93%
“…Our study, in accordance to the work of other research groups (Esperer and Oehler 2010, Karmakar et al 2009, Piskorski and Guzik 2007, Porta et al 2008, clearly detected HRA. According to our investigation, HRA is the reflection of and could be influenced by the ratio of inspiration/expiration duration.…”
Section: Discussionsupporting
confidence: 93%
“…The abnormalities that observed in the restitution steeper and Lorenz plots indicated that there are alterations in the effective refractory periods and the influences of the autonomic tone on the beat to beat interval. [22232425] This observation documented the experimental study used rat in which tonic convulsive seizures played a role on the distortion of the cardiac autonomic regulation and thereby induced changes in the duration of cardiac arrhythmia. [26] One of the limitations of the study is the genetic study did not carry to link between the patients who are vulnerable to cardiac arrhythmias with the mutation of certain genes.…”
Section: Discussionmentioning
confidence: 96%
“…Heart rate asymmetry (HRA) was initially described as a visible phenomenon, mostly present in healthy subjects, which can be assessed by visual inspection using a Poincaré plot (Guzik et al 2006, Karmakar et al 2009, Piskorski and Guzik 2007, 2011. Various approach exists for defining HRA using Poincaré plot (Guzik et al 2006, Karmakar et al 2009, Esperer and Oehler 2010. According to Guzik et al, HRA is defined as the imbalance of acceleration and deceleration of heart rate (Guzik et al 2006).…”
Section: Introductionmentioning
confidence: 99%